QUALITY OF SOIL TILLAGE PERFORMED WITH A HYDRAULIC EXCAVATOR AND A TRACTOR IN SLOPED AREAS - Fernanda Leite Cunha; Erick Martins Nieri; Rodolfo Soares de Almeida; Lucas Amaral de Melo; Fernando Palha Leite (Revista Árvore)
ABSTRACT Studies addressing the mechanization of forestry in slope areas are scarce because of the difficulties to access those areas and the cost of the activity. A recent adaptation using a hydraulic excavator for soil tillage in sloped areas has shown positive results mainly obtained due to the benefits provided by the increase in subsurface area. However, little is known about its effect on the quality and efficiency of the activity. Therefore, the objective of this study was to evaluate the soil tillage quality performed by a hydraulic excavator and a subsoiler attached to a tractor during the dry and rainy seasons, in the presence (PW) or absence of a wing (AW) in the chisel of the subsoiling tines in sloped areas. We evaluated the depth, the surface width, the mobilized soil area, the profile of the tilled soil, and the quality of clod breakdown. Soil preparation in the rainy season is approximately double the prepared area compared to the second period. In addition, the presence of the wing on the tip of the subsoiler rod contributes to increase the mobilized soil area and consequently increased soil clods, thereby indicating the quality of the preparation, especially in the dry season. The hydraulic excavator mobilizes the soil with higher averages than those recommended for inclined areas due to its mechanical power, while the subsoiler maintains the preparation within the expected averages. Despite the peculiarities of each implement, they both present quality soil performances.